The Role of Women Journalists in Media - Putra, Adrian Nuzul; Lani, Oktri Permata (AGENDA: Jurnal Analisis Gender dan Agama, 2022)
Becoming a journalist is not easy, especially for female journalists, if they journalist is sent to cover conflict areas, such as reporting on demonstrations, wars, and even criminal cases. Indirectly, psychologically, when women are faced with things that are raging with more masses, it is necessary to have quite high mental and physical strength. That way, working as a journalist is very high risk because you have to have the courage to sacrifice between life and death to get to the truth. On the other hand, a journalist is also required to be professional in carrying out his duties properly and correctly and commit to improving a journalist's capabilities. The type of research used is qualitative, namely, research that produces information in the form of notes and descriptive data contained in the text under study (Mantra, 2008: 30). Journalist professionalism is a job that aims to find information that is then disseminated based on rules and norms that apply to a journalist when carrying out his duties.The problems between the domestic sphere and his profession as a journalist are endless and of course, it is a challenge in itself. In addition, there is still discrimination from companies against female journalists, such as giving inappropriate wages. With coverage, you have to take risks that need to be maintained, such as information from sources that must be accurate, especially when there is a lot of coverage that does not comply with the protocol. Working as a journalist is very hard, apart from getting news, journalists also risk their lives for news from anywhere.